2023
DOI: 10.1111/mpp.13311
|View full text |Cite
|
Sign up to set email alerts
|

Tomato chlorosis virus p22 interacts with NbBAG5 to inhibit autophagy and regulate virus infection

Abstract: Tomato chlorosis virus (ToCV) is a member of the genus Crinivirus in the family Closteroviridae . It has a wide host range and wide distribution, causing serious harm to the vegetable industry. The autophagy pathway plays an important role in plant resistance to virus infection. Viruses and plant hosts coevolve in defence and antidefence processes around autophagy. In this study, the interaction between ToCV p22 and Nicotiana benthamiana B‐ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…According to the plasmid construction method used in our laboratory ( Shang et al., 2023 ), the StlncRNA13558 gene was ligated to the restriction site region between the 35S promoter and Nos terminator of the pCa plasmid to obtain the pCa- StlncRNA13558 overexpression plasmid. The StPRL gene was ligated to the restriction site region between the 35S promoter and the Nos terminator of the pCa-GFP plasmid to obtain the pCa-StPRL-GFP overexpression plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…According to the plasmid construction method used in our laboratory ( Shang et al., 2023 ), the StlncRNA13558 gene was ligated to the restriction site region between the 35S promoter and Nos terminator of the pCa plasmid to obtain the pCa- StlncRNA13558 overexpression plasmid. The StPRL gene was ligated to the restriction site region between the 35S promoter and the Nos terminator of the pCa-GFP plasmid to obtain the pCa-StPRL-GFP overexpression plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…One such example is observed in the case of tomato chlorosis virus (ToCV) infection. The P22 protein of ToCV interacts with the N. benthamiana B-cell lymphoma2-associated athanogenes5 (NbBAG5), an evolutionarily conserved protein mainly involved in plant growth and stress response, and induces NbBAG5 expression, leading to the inhibition of autophagy and favoring viral infection [ 74 ]. Another report revealed that the interaction of P3 and/or P3N-PIPO of PVY with BI-1 decreases the expression of the ATG6, thereby inhibiting the autophagic degradation of viral NIb and enhancing viral replication [ 75 ].…”
Section: Autophagy–virus Interplay In Plants: From Antiviral Recognit...mentioning
confidence: 99%
“…Autophagy also targets plant viruses and it is a major player in antiviral innate immunity [69][70][71][72][73][74][75]. Several plant viruses manipulate the autophagy machinery to inhibit antiviral defenses in plants [76][77][78][79][80]. However, plant viruses also exploit autophagy for pro-viral functions [65,81,82].…”
Section: Introductionmentioning
confidence: 99%